Examining learning from failure to venture growth: Empirical study in hospitality SMEs in Indonesia - Dorojatun Prihandono; Kris Brantas Abiprayu; Angga Pandu Wijaya; Norain Ismail (Jurnal Manajemen dan Pemasaran Jasa, 2024)
This study investigates the crucial role of learning from failure in shaping venture growth within the context of the hospitality industry, particularly in light of recent challenges posed by increasingly complex and competitive external factors. The hospitality industry has been the most severely affected by the crisis, making it a relevant context for research. Employing a quantitative approach, the study examines the influence of emotions, narcissism, and stock of knowledge on learning from failure and its subsequent impact on venture growth. A total of 161 respondents, all owners of SMEs in the hospitality sector, completed the questionnaire. The data obtained were analyzed using variance-based structural equation modeling (VB-SEM). The results indicate that while emotions and narcissism present obstacles and opportunities for learning, a strong stock of knowledge positively affects learning from failure and venture growth. However, the study shows that narcissism does not directly influence venture growth but does so indirectly through learning from failure. These findings underscore the importance of fostering a culture that embraces failure as a catalyst for innovation and resilience in adversity. The study contributes valuable insights into the dynamics of learning from failure and its implications for entrepreneurial success in the hospitality industry.